Ketamine Within Clinically Effective Range Inhibits Glutamate Transmission From Astrocytes to Neurons and Disrupts Synchronization of Astrocytic SICs - Zhang, Yu; Wu, Sisi; Xie, Liwei; Yu, Shouyang; Zhang, Lin; Liu, Chengxi; Zhou, Wenjing; Yu, Tian (Frontiers in Cellular Neuroscience, 2019)
Background Astrocytes are now considered as crucial modulators of neuronal synaptic transmission. General anesthetics have been found to inhibit astrocytic activities, but it is not clear whether general anesthetics within the clinical concentration range affects the astrocyte-mediated synaptic regulation. Methods The effects of propofol, dexmedetomidine, and ketamine within clinically effective ranges on the slow inward currents (SICs) were tested by using the whole-cell recording in acute prefrontal cortex (PFC) slice preparations of rats. Astrocytes culture and HPLC were used to measure the effects of different anesthetics on the glutamate release of astrocytes. Results Propofol and dexmedetomidine showed no significant effect on the amplitude or frequency of SICs. Ketamine was found to inhibit the frequency of SICs in a concentration-dependent manner. The SICs synchronization rate of paired neurons was inhibited by 30 μM ketamine (from 42.5 ± 1.4% to 9.6 ± 0.8%) and was abolished by 300 μM ketamine. The astrocytic glutamate release induced by DHPG, an agonist of astrocytic type I metabotropic glutamate receptors, was not affected by ketamine, and ifenprodil, a selective antagonist of GluN1/GluN2B receptor, blocked all SICs and enhanced the inhibitory effect of 30 μM ketamine on the frequency of SICs. Ketamine at low concentration (3 μM) could inhibit the frequency of SICs, not the miniature excitatory postsynaptic currents (mEPSCs), and the inhibition rate of SICs was significantly higher than mEPSCs with 30 μM ketamine (44.5 ± 3% inhibition vs. 28.3 ± 6% inhibition). Conclusion Our data indicated that ketamine, not propofol and dexmedetomidine, within clinical concentration range inhibits glutamatergic transmission from astrocytes to neurons, which is likely mediated by the extrasynaptic GluN1/GluN2B receptor activation.